The effect of irrigation and cropping systems on soil carbon and nitrogen stocks and organic matter aggregation in semi-arid lands - Abulobaida, Mohamed, author; Davis, Jessica G., advisor; Hansen, Neil, committee member; Cotrufo, M. Francesca, committee member; Conant, Richard T., committee member; Barbarick, Kenneth A., committee member (Colorado State University. Libraries, 2014)
Demand for water is increasing as a result of population growth, economic activity and agricultural irrigation requirements. Thus, the balance between water demand and supply becomes unstable in countries suffering from water shortage. Therefore, overuse of non-rechargeable groundwater for irrigation in arid regions reduces the availability of water for other users. However, increasing drought periods, shortages of groundwater and urban competition for water have altered irrigated agriculture in Colorado. This may lead to changes in irrigated cropping practices such as alternative water conservation approaches from full irrigation to limited irrigation or dryland cropping systems to alleviate shortage. However, the risk of loss of soil C from dewatered cropland exists, because soil C levels may decline with reduced irrigation due to decreased C input into the soil. The overall goal of the study is to evaluate the impact of conversion from full irrigation to no- till limited irrigation or dryland cropping systems on soil carbon and nitrogen stocks and organic matter aggregation in semi-arid lands. This goal was achieved in the context of three studies that are included in this dissertation. First, the impact of irrigation and cropping systems management on SOC and TN stocks in a semi-arid environment was evaluated for wheat (Triticum aestivum), corn (Zea mays), and alfalfa (Medicago sativa) managed under various treatments of full irrigation, limited irrigation and dryland cropping systems. Second, the effect of different cropping systems with various irrigation levels and dryland cropping on soil aggregation and physical SOC stabilization in a semi-arid region was evaluated by measuring the aggregate size distribution, determining the C and N stocks in aggregate fractions and measuring the soil C mineralization rate in different cropping systems with various irrigation levels. Finally, the impact of conversion of irrigated farmland to limited irrigation or dryland cropping systems on SIC content was evaluated over a 3-yr period. The SOC and TN were analyzed at different depths from 0 to 60 cm depth in 2007 and 2010. Aggregate size distribution, SOC and TN contents for the aggregate size fractions [macro (M) and micro (m) aggregates, and silt & clay fractions] and for the isolated fractions from macroaggregates [coarse particulate organic matter (cPOM), microaggregate into macroaggregate (mM) and Silt&Clay-M)] were measured in soils from full irrigation alfalfa (Full-A), full irrigation corn (Full-C), limited irrigation forage alfalfa (Ltd-fA), limited irrigation forage corn (Ltd-fC), limited irrigation grain wheat (Ltd-gW), limited irrigation grain corn (Ltd-gC), dryland wheat (Dry-W) and dryland corn (Dry-C) treatments. SIC was measured in 2007 and 2010 for all treatments, and in 2013 for limited irrigation grain wheat-corn sorghum cropping system (Ltd-gWCFs). Soil pH was measured for all treatments in 2010 and for Ltd-gWCFs in 2013 in the different depths. The SOC and TN contents were significantly different among full irrigation and dryland treatments in the 0-20 cm layers of soil, but those differences were not significant below 20 cm depth. However, for all treatment comparisons, the differences remained significant throughout the soil profile in which crops rotated with alfalfa particularly limited irrigation systems (Ltd-fA and Ltd-fC) had higher SOC and TN stock compared with Ltd-gW. Our results showed the SOC and N stocks were significantly related to their concentrations not to bulk density for all depths. The SOC and TN distribution throughout the soil profile were stratified, and the SOM accumulation under the treatments almost occurred at similar C/N ratios. The amount of free microaggregates (m) under all treatments ranged from 69.4 to 75.6 % of the soil and the macroaggregates (M) comprised less than 18 % of the soil. The latter was higher under fully irrigated corn (Full-C), limited irrigation forage corn (Ltd-fC) and limited irrigation grain corn (Ltd-gC) compared to dryland corn (Dry-C). The SOC stock in the microaggregates occluded inside macroaggregates (mM) was higher under fully irrigated crops relative to dryland crops, especially in corn treatments. Conversion from full irrigation to dryland induced a reduction in macroaggregates. The Full-C treatment had higher SOC stocks in mM fraction relative to Dry-C. Our study indicates that irrigation and no-till management enhanced aggregate formation and increased C sequestration in mM fractions compared to dryland cropping systems. The SIC stock was significantly higher under limited irrigation grain wheat (Ltd-gW) treatments compared to full irrigation cropping systems (Full-C and Full-A) and limited irrigation forage cropping systems (Ltd-fC and Ltd-fA). However, there were no significant differences between Ltd-gW and other treatments (Ltd-gC, Dry-C and Dry-W). The Ltd-gW treatment gained more SIC compared to other treatments which accounted 19.4 % of total SIC sequestered under all treatments over the entire profile (0-60 cm) through the period of the study. Our results showed that the most important factor controlling the process of SIC formation in the 0-30 cm depth was soil pH which explains the high variation of SIC among treatments (R2 = 0.80, P <.01). This may be due to the effect of different cropping systems in which sunflower rotated into wheat-corn grain rotation (Ltd-gWCSf) consumed a greater amount of water than other summer crops and this may be effectively increasing soil pH in those crops rotated with sunflower.